ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT WAJIB PAJAK DALAM PELAPORAN SPT TAHUNAN MELALUI E-FILLING ( STUDI EMPIRIS PADA KPP PRATAMA TEGAL ) - Asrofi Langgeng Noerman syah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
This study aimed to determine the effect of the security and privacy, information technology readiness, perceived usefulness, and perceived ease the interest of the taxpayer in the annual tax return reporting via e-filling on KPP Pratama Tegal. This research subject is an individual taxpayer employees listed on KPP Pratama Tegal. Selected samples were 94 respondents using purposive sampling technique. Data obtained by distributing questionnaires. Analysis of data using multiple linear regression, and to determine the hypothesis used t-test and F-test. Results showed the security and privacy of variables and variables perceived ease significantly influence of taxpayer interest in reporting their annual tax return via e-filling on KPP Pratama Tegal. Meanwhile, variable information technology and variable readiness perception of usefulness does not affect the interest of the taxpayer in the annual tax return reporting via e-filling on KPP Pratama Tegal.